Mapping the Scientific Landscape of Water Footprint in Agriculture: A Global Bibliometric Analysis - , Jwngsar Moshahary; , Mrinal Choudhury; , Bhaskarjyoti Sarma; , Pompy Deka; , Perves Ahmed; , Britan Rahman; , Subhankar Saha; , Hrishikesh Ojah; , Prasanta Kumar Das; , Rupak Kumar Nath (Archives of Current Research International, 2025)
The study presents a systematic bibliometric analysis of agricultural water footprint research all over the world. A total of 2,084 journal articles published during the year 2000 to 2024 were collected and catalogued using lens.org platform. Water footprint, blue water, green water, and grey water in the context of agriculture were the terms employed for selecting the articles. The dataset was subjected to advanced filtering and refinement using the processing techniques in R. VOSviewer (v1.6.20) was used for depicting the key research trends, influential academics, and cooperative networks that shaped the field in the bibliometric maps. The results showed that the number of publications has increased at the CAGR of 21.97% since 2010, reflecting growing global concerns about sustainable water management in agriculture. Co-authorship and citation analysis highlight the contributions of Arjen Y. Hoekstra, Mesfin Mekonnen and Johan Rockström, while the co-occurrence mapping of keywords highlights the critical intersections with climate change, life cycle assessment, and virtual water. Publishing and funding areas were dominated by major publishers such as Elsevier, MDPI, Springer and supported by a variety of global funding bodies, strengthening collaborative research ecosystems.